Nonlinear science and complexity - Dai, Liming, 1961-; Hamidzadeh, H. R. (Hamid R.); Luo, Albert C. J. (Transactions of nonlinear science and complexity, 2007)
This volume provides useful tools in Lie group analysis to solve nonlinear partial differential equations. Many of important issues in nonlinear wave dynamics and nonlinear fluid mechanics are presented: Homotopy techniques are used to obtain analytical solutions; fundamental problems and theories in classic and quantum dynamical systems are discussed; and numerous interesting results about dynamics and vibration in sensor and smart systems are presented. Interval computation and nonlinear modeling in dynamics and control are also briefly included. Sample Chapter(s). Chapter 1: Symmetry reduct.